On the species composition of the robber flies (Diptera: Asilidae) based on analysis of samples from central Vietnam - Thinh, Ta Huy; Nhi, Pham Thi (Academia Journal of Biology, 2014)
A total of 27 species belonging to 4 subfamilies of robber flies (Asilidae: Diptera) are currently known from Vietnam. This paper deals with the result of the first study on the species composition of Robber flies from four provinces in Central Vietnam: Quang Binh, Quang Tri, Thua Thien - Hue, and Quang Nam collected during the time from 2004 to 2006. Specimens of Robber flies were collected mainly from natural habitats and at altitude range from 300 up to 1100 m a.s.l. This study provided a list of 64 species belonging to 32 genera and 5 subfamilies recorded in central Vietnam, including 25 recognisable taxonomic units which open up a whole range for the description of new species. Of which 31 species and 9 genera including Ammophilomima, Goneccalypsis, Laphystina, Merodontina, Michotamia, Neoitamus, Neolaparus, Philonicus, and Scylaticus as well as subfamily Leptogastrinae are newly recorded for the Asilidae fauna of Vietnam. The Robber fly fauna of Central Vietnam is characterized by the species richness of the genus Ommatius (Ommatini, Asilinae); Philodicus and Promachus (Apocleini, Asilinae); Damalis (Damalini, Trigonominae) and Choerades (Laphriini, Laphrinae). Of the genus Microstylum (Saropogonini, Dasypogoninae), besides two common species Microstylum dux (Wiedemann) and Microstylum oberthueri Wulp, other two species Microstylum sp.1 and Microstylum sp.2 were recorded. Of the genus Eultolmus (Asilini, Asilinae), Eutolmus sp.1. was found but not Eutolmus maximus Hradsky et Geller-Grimm, 1998. robber flies of Ommatius scinius Oldroyd; Philodicus fuscipes (Ricardo); Philodicus longipes Schiner; Promachus apicalis (Macquart); Astochia enermis Hermann; Machimus aurimystax (Bromley); Damalis vittripennis Osten-Saken; Microstylum sp.2; Choerades conopoides Oldroyd; Maira aurifacies (Macquart), and Pagidolaphria gigas (Macquart) are collected concurrently in the forest and the agricultural habitats; whereas another species found only in the natural habitats. Key to the 32 genera of Asilidae is also compiled.